المتون الفقهية و اثرها في مناهج التدريس - بن مايدي حسام; سلمات علي; د/ ورنيقي محمد (جامعة عمار ثليجي الاغواط, 2024)
الملخص جاء هذا البحث في مقدمة وثلاثة مباحث، ومداره حول المتون الفقهية والتي تعتبر من الأمور المهمة التي ينبغي عدم الإغفال عنها، لمالها من أهمية كبيرة، حيث أنها تتعلق بمصادر الأحكام وأدلتها، والتي لقت جدلا كبيرا بين الفقهاء . الإشكالية: هل المتون الفقهية حجة شرعية ودليل يحتكم إليه كسائر الأدلة أم لا؟. وقد اختلف الفقهاء فيها إلى تقسيمات ثلاث : فهناك من لم يعتبرها حجة وإنما هي مجرد قرينة .وهناك من الفقهاء من اعتبرها حجة وعمل بها وطبقها في استخراج الأحكام.وهناك من فصل في ذلك واعتبرها حجة لكن بشروط وضوابط وأكثرهم المعاصرين . أهم النتائج المتوصل إليها: إن المتون الفقهية ليست على درجة واحدة من حيث الاحتجاج، بل تنقسم إلى متفق عليها ومختلف فيها، ولهذا كانت هذه الأخيرة أحد أسباب اختلاف الفقهاء في حجيتها. أغلب المتون الفقهية تبنتها المذاهب الاجتهادية في تفريع الأحكام وتنزيل الحوادث عليها، وتخريج الحلول الشرعية للوقائع، وقد اتضح ذلك من خلال المسائل المستدل عليها بالقواعد الفقهية. الكلمات المفتاحية: المتون الفقهية ، الضابط الفقهي، الحجية. Summary This research comes in an introduction and three studies, and its orbit on the authority of the jurisprudential rule, which is an important thing that should not be overlooked, is of great importance because it is related to the sources of the judgments and their evidence, which have generated great controversy among scholars. Problematic: Is the jurisprudential rule a legitimate argument and a guide to the same as other evidence or not ?. The fuqaha 'have differed on three categories: There are those who did not consider it an argument but rather a presumption. Some of the jurists considered it an argument and worked on it and applied it to extract sentences. There is a chapter in that and considered it an argument, but under conditions and controls and most of them contemporary. Key findings: The jurisprudential rule is not one degree in terms of protest, but divided into an agreed upon and different, and this was one of the reasons why the scholars differed in their argument. Most of the jurisprudential rules adopted by the doctrines of jurisprudence in the division of judgments and the reduction of incidents on them, and the graduation of legitimate solutions to the facts, and this has been clear through the issues based on jurisprudence rules. Keywords: jurisprudential rule, fundamentalist rule, jurisprudential officer, authoritative